A biological shell material phase change microcapsule and preparation method thereof

By using biological shell material as shell material, combined with high-speed shearing treatment and esterification reaction, bioshell phase change microcapsules with thermal storage and temperature control, antibacterial and anti-inflammatory, antioxidant and anti-ultraviolet radiation functions were prepared, solving the problems of poor room temperature thermal storage and temperature control effects and high production costs in the prior art.

CN115612455BActive Publication Date: 2025-04-01CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202110803709.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-07-16
Publication Date
2025-04-01
Estimated Expiration
2041-07-16

AI Technical Summary

Technical Problem

The existing phase change microcapsules lack obvious heat storage and temperature control effects at room temperature, and the operation process is complicated, which increases production costs.

Method used

The bioshell material is used as the shell material, and the molten phase change material is mixed with the shell material prepolymer, nonionic surfactant and mixed solvent, and high-speed shearing treatment and esterification reaction are carried out to form a stable bioshell phase change microcapsule.

Benefits of technology

The bioshell phase-change microcapsules have the function of thermal storage and control at room temperature, and give them antibacterial and anti-inflammatory, antioxidant and anti-ultraviolet radiation, and have outstanding mechanical strength, reducing production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115612455B_ABST
    Figure CN115612455B_ABST
Patent Text Reader

Abstract

The present invention discloses a biological shell material phase change microcapsule and a preparation method thereof. The preparation method of the biological shell material phase change microcapsule provided by the present invention comprises the following steps: (1) uniformly mixing a molten phase change material, a shell material prepolymer A, a nonionic surfactant and a mixed solvent, and subjecting the mixture to high-speed shearing treatment to obtain a phase change microemulsion; (2) stirring the phase change microemulsion obtained in step (1) to react under heating, and simultaneously dripping a mixed solution containing a shell material prepolymer B to obtain a solid-liquid mixture; (3) filtering, washing and drying the solid-liquid mixture obtained in step (2) to obtain a biological shell material phase change microcapsule. The biological shell material phase change microcapsule obtained by the preparation method provided by the present invention has the functions of heat storage and temperature control, and also has the functions of antibacterial and anti-inflammatory, anti-oxidation and anti-ultraviolet radiation. In addition, it also has outstanding mechanical strength, which broadens its scope of application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of phase change energy storage materials, and specifically relates to a biological shell material phase change microcapsule and a preparation method thereof. Background Art

[0002] Phase change materials are a type of material that can store heat or cool by changing its own phase state as the ambient temperature changes. They are widely used in heat exchange and storage due to their high energy storage density, low cost, and good chemical stability. In order to avoid the leakage problem of phase change materials, Barret K proposed microencapsulation technology in the 1950s. Phase change microcapsules use phase change materials as core materials and encapsulate them with shell materials. According to the particle size of the capsule, they are divided into nanocapsules (<1μm), micron capsules (1μm~1mm), and macrocapsules (1mm~1cm). Microencapsulated phase change materials have the advantages of larger heat transfer area, reduced reactivity with the external environment, and controllable volume during the phase change stage.

[0003] In microencapsulation technology, the choice of shell material and preparation process directly determines the performance and application range of microcapsules. Currently, the most widely used microcapsule shell materials are mainly polymer materials (melamine formaldehyde resin, etc.), inorganic materials (silicon dioxide, calcium carbonate, etc.), and polymer-nanoparticle hybrid materials. However, these materials have more or less disadvantages such as high toxicity, poor toughness, and short service life. Studies have shown that compared with existing shell materials, biological shell materials have the advantages of no toxicity, good toughness and strength, and biological properties such as antibacterial and antiviral.

[0004] CN111992153A discloses a method for preparing high-load and high-thermal stability menthol microcapsules. The aqueous phase is prepared with octenyl succinate starch, the oil phase is prepared with lipids and menthol, the oil phase is poured into the aqueous phase, homogenized and then high-pressure homogenized, and spray-dried after cooling, with a cooling rate of 0.5°C / min to 1.5°C / min. The microcapsules prepared by this method mainly use menthol as the core material and lipid-modified starch as the wall material, and do not have obvious room temperature phase change temperature regulation effect. In addition, the operation process requires the use of technical means such as high-pressure homogenization and spray drying, which significantly increases the production cost of microcapsule products.

[0005] CN105077249A discloses a method for preparing conjugated linoleic acid microcapsules. First, the raw materials are prepared according to the weight ratio of conjugated linoleic acid: modified edible starch: water in a ratio of 1:1:3, and the raw materials are added into the kettle for emulsification reaction for 30 minutes; then the emulsion is added into the high-speed homogenizer for shear emulsification, and the feed pressure is ≤10MPa. When the pressure reaches 8MPa~10MPa, the material is switched to the spray metering kettle, and spraying is started after homogenization. When the temperature reaches 250℃, the feed is started, and the outlet temperature is controlled at 90℃~120℃ to ensure continuous temperature feeding. The microcapsules prepared by this method use conjugated linoleic acid as the core material and modified edible starch as the wall material. They do not have obvious room temperature heat storage and temperature control functions, nor can they exert the beneficial effects of bio-based materials (conjugated linoleic acid) in natural environments. Moreover, the operating conditions are harsh, which increases production costs. Summary of the invention

[0006] In order to overcome the shortcomings of the prior art, the present invention provides a bioshell phase-change microcapsule and a preparation method thereof. The bioshell phase-change microcapsule obtained by the preparation method provided by the present invention not only ensures that it has the function of heat storage and temperature control, but also has the functions of antibacterial and anti-inflammatory, anti-oxidation and anti-ultraviolet radiation. In addition, it also has outstanding mechanical strength, which broadens its application scope.

[0007] The first aspect of the present invention provides a method for preparing a bioshell material phase change microcapsule, comprising the following steps:

[0008] (1) The molten phase change material, the shell material prepolymer A, the nonionic surfactant and the mixed solvent are uniformly mixed and subjected to high-speed shear treatment to obtain a phase change microemulsion;

[0009] (2) stirring the phase change microemulsion obtained in step (1) under heating to react, and simultaneously adding dropwise a mixed solution containing the shell material prepolymer B to obtain a solid-liquid mixture;

[0010] (3) The solid-liquid mixture obtained in step (2) is filtered, washed, and dried to obtain bioshell material phase change microcapsules.

[0011] Furthermore, in step (1), the phase change material is selected from one or more of normal alkanes, paraffins, and stearates with a phase change temperature of 20°C to 30°C, preferably paraffin.

[0012] Furthermore, in step (1), the shell material prepolymer A is selected from one or more of levomenthol, dextromenthol, and racemic menthol, preferably levomenthol.

[0013] Furthermore, in step (1), the nonionic surfactant is selected from one or more of polyethylene glycol 200, polyethylene glycol 400, and polysorbate 20, preferably polyethylene glycol 200.

[0014] Furthermore, in step (1), the mixed solvent is selected from one or more of ethanol aqueous solution, chloroform aqueous solution, and acetone aqueous solution, preferably ethanol aqueous solution, wherein the mass ratio of ethanol to water is 1: (5-15), preferably 1: (7-10).

[0015] Furthermore, in step (1), the mass ratio of the phase change material, shell material prepolymer, nonionic surfactant and mixed solvent is 1: (0.1-0.8): (0.01-0.07): (15-35), preferably 1: (0.3-0.5): (0.03-0.05): (20-30).

[0016] Furthermore, in step (1), the high-speed shearing treatment is performed at a temperature of 50°C to 90°C for 3 to 20 minutes, and a shearing speed of 7000 rpm to 15000 rpm; the shearing temperature is preferably 65°C to 75°C, and the shearing time is preferably 7 to 12 minutes. The shearing speed is preferably 9000 rpm to 13000 rpm.

[0017] Furthermore, in step (2), the stirring reaction speed is 400 rpm to 700 rpm, preferably 500 rpm to 600 rpm. The heating temperature is 60° C. to 90° C., preferably 70° C. to 80° C. The stirring reaction time is 1 h to 5 h, preferably 2.5 h to 3.5 h.

[0018] Furthermore, in step (2), the shell material prepolymer B is selected from one or more of α-linolenic acid, γ-linolenic acid, and linoleic acid, preferably α-linolenic acid. The mixed solution containing shell material prepolymer B is a mixed solution of shell material prepolymer B and anhydrous ethanol, and the mass concentration of shell material prepolymer B in the mixed solution is 35% to 70%, preferably 45% to 55%. Relative to each liter of phase change microemulsion, the dripping rate is 2g / min to 20g / min, preferably 10g / min to 14g / min. Among them, the concentration of the mixed solution containing shell material prepolymer B refers to the concentration of shell material prepolymer B in the mixed solution.

[0019] Furthermore, in step (2), the mass ratio of the shell material prepolymer B to the shell material prepolymer A in step (1) is 1:(0.35-0.95), preferably 1:(0.5-0.7).

[0020] Furthermore, in step (3), the solid-liquid mixture obtained in step (2) can be washed with an organic solvent, and the organic solvent is selected from one or more of ethanol, acetone, and chloroform, preferably ethanol. The drying temperature is 45° C. to 100° C., preferably 55° C. to 65° C. The drying time is 12 h to 48 h, preferably 20 h to 30 h.

[0021] The second aspect of the present invention provides a biological shell material phase change microcapsule obtained by the above preparation method.

[0022] Furthermore, the particle size of the bioshell phase-change microcapsules is 5 μm to 20 μm, the latent heat of fusion is 100 J / g to 120 J / g, the coverage is 66.3% to 79.6%, and the thermal conductivity is 0.33 W·m -1 ·k -1 ~0.45W·m -1 ·K -1 , the compressive strength is 1MPa~2MPa.

[0023] Furthermore, the antibacterial property of the biological shell material phase change microcapsule is 60% to 70% in inhibition rate against Staphylococcus aureus, 65% to 75% in scavenging DPPH free radicals (i.e., antioxidant capacity), and 1.4 to 1.8 in long-wave ultraviolet absorbance (anti-ultraviolet radiation capacity).

[0024] The third aspect of the present invention provides a bioshell phase change microcapsule obtained by the above preparation method for use in the fields of building heat storage and temperature regulation, indoor air purification, and object anti-oxidation or anti-ultraviolet radiation.

[0025] Compared with the prior art, the present invention has the following advantages:

[0026] (1) The preparation method of the biological shell material phase change microcapsule provided by the present invention comprises the following steps: in step (1), an emulsification reaction is carried out. At this stage, the shell material prepolymer A is selected from menthol as the shell material prepolymer to be blended with the molten phase change core material. Since menthol has both hydroxyl and cyclohexyl structures, it has oil and water amphiphilic properties, that is, it can be used as a surfactant and tightly combined with the molten phase change core material, thereby helping to form a stable pre-coated structure. Subsequently, a strong wall material structure is generated through the esterification reaction of the shell material prepolymer A and the shell material prepolymer B, thereby effectively encapsulating the molten phase change core material.

[0027] (2) The bioshell phase-change microcapsules prepared by the present invention, while ensuring that they have the function of heat storage and temperature control, also give them the functions of antibacterial and anti-inflammatory, anti-oxidation and anti-ultraviolet radiation according to the different structural units of the two bioshell materials, thereby broadening their scope of application. Moreover, since the bioshell phase-change microcapsules prepared by the present invention have shell materials that are esterification products and contain long-chain alkyl and cyclohexyl structural units, they have better mechanical strength than other bio-based phase-change microcapsules (such as starch).

[0028] (3) The preparation process of the present invention is simple, the operation process is safe and environmentally friendly, and the synthesis reaction time period is short, which is suitable for mass production. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is a scanning electron microscope photo (SEM) of the bioshell material phase change microcapsule prepared in Example 1;

[0030] Figure 2 This is a scanning electron microscope photo (SEM) of the bioshell material phase change microcapsule prepared in Example 2;

[0031] Figure 3 This is a scanning electron microscope photo (SEM) of the bioshell phase change microcapsule prepared in Comparative Example 1;

[0032] Figure 4 This is a scanning electron microscope photo (SEM) of the bioshell phase change microcapsule prepared in Comparative Example 2;

[0033] Figure 5 The differential scanning calorimetry (DSC) curves of paraffin, biological shell material phase change microcapsules prepared in Example 1 and Comparative Example 1. DETAILED DESCRIPTION

[0034] The following examples further illustrate the preparation method and effect of the bioshell phase-change microcapsules of the present invention. The examples are implemented based on the technical solution of the present invention, and provide detailed implementation methods and specific operation processes, but the protection scope of the present invention is not limited to the following examples.

[0035] The experimental methods in the following examples, unless otherwise specified, are all conventional methods in the art. The experimental materials used in the following examples, unless otherwise specified, were purchased from conventional biochemical reagent stores.

[0036] In the present invention, a Japanese Hitachi S-4700 field emission scanning electron microscope (SEM) is used to observe the morphology and particle size of the biological shell material phase change microcapsules.

[0037] In the present invention, a differential scanning calorimeter (DSC) is used to test the latent heat of phase change of the bioshell material phase change microcapsule during the melting process. The instrument model is DSC-60 Plus of Shimadzu Corporation of Japan. Under a nitrogen atmosphere, the temperature test range is -20°C to 50°C, the heating rate is 10°C / min, and the sample weight is about 3.5 mg.

[0038] In the present invention, the thermal conductivity of the biological shell material phase change microcapsule sample is measured using a DRL-III-P thermal conductivity tester produced by Xiangyi Instrument Co., Ltd.

[0039] In the present invention, the compressive strength of the biological shell material phase change microcapsule sample is measured using a YL-C10K pressure testing machine produced by Guangdong Yuelian Instrument Co., Ltd.

[0040] In the present invention, the calculation formula for the coverage rate of phase change microcapsules is:

[0041] Coverage rate / % = (latent heat of melting of microcapsules / latent heat of melting of phase change materials) × 100%.

[0042] In the present invention, the antibacterial property test of Staphylococcus aureus is carried out with reference to the oscillation method in GB / T-2008, and the DPPH free radical scavenging ability (i.e., antioxidant ability) and long-wave ultraviolet absorbance (anti-ultraviolet radiation ability) tests are carried out with reference to the method provided in "Food Industry" 2020, 41 (6): 201-204.

[0043] Example 1

[0044] Take 10g of paraffin with a molten phase transition temperature of 25°C, 4g of levomenthol, 0.4g of polyethylene glycol 200 and 250g of ethanol aqueous solution and mix them, wherein the mass ratio of ethanol to deionized water is 1:8. At 65°C and 9000rpm, high-speed shear reaction is carried out for 10 minutes to obtain a phase change microemulsion. Pour the phase change microemulsion into a three-necked flask, move it to an electric heating jacket with a mechanical stirrer, and stir the reaction at 75°C and 550rpm for 3 hours. At the same time, 13.3g of α-linolenic acid ethanol mixed solution is added dropwise at a rate of 3g / min. The mass concentration of the α-linolenic acid ethanol mixed solution is 50%. The obtained solid-liquid mixture is filtered and rinsed with ethanol. The filtrate is placed in a forced air drying oven at 60°C for 24 hours to obtain bioshell phase change microcapsules. The scanning electron microscope (SEM) photograph of the bioshell phase change microcapsules prepared in Example 1 is shown in Figure 1 The differential scanning calorimetry (DSC) curve of the bioshell phase change microcapsules prepared in Example 1 is shown in Figure 5 .

[0045] Example 2

[0046] Take 10g of paraffin with a molten phase transition temperature of 25°C, 3g of levomenthol, 0.3g of polyethylene glycol 200 and 200g of ethanol aqueous solution and mix them, wherein the mass ratio of ethanol to deionized water is 1:7. At 70°C and 11000rpm, high-speed shear reaction is carried out for 7 minutes to obtain a phase change microemulsion. Pour the phase change microemulsion into a three-necked flask, move it to an electric heating jacket with a mechanical stirrer, and stir the reaction at 70°C and 500rpm for 2.5 hours. At the same time, 13.3g of α-linolenic acid ethanol mixed solution is added dropwise at a rate of 2.5g / min. The mass concentration of the α-linolenic acid ethanol mixed solution is 45%. The obtained solid-liquid mixture is filtered and rinsed with ethanol. The filtrate is placed in a forced air drying oven at 55°C for 20 hours to obtain bioshell material phase change microcapsules. The scanning electron microscope (SEM) photograph of the bioshell material phase change microcapsules prepared in Example 2 is shown in Figure 2 .

[0047] Example 3

[0048] Take 10g of paraffin with a molten phase transition temperature of 25℃, 5g of L-menthol, 0.5g of polyethylene glycol 200 and 300g of ethanol aqueous solution, wherein the mass ratio of ethanol to deionized water is 1:10. At 75℃ and 13000rpm, high-speed shear reaction is carried out for 12min to obtain a phase-change microemulsion. Pour the phase-change microemulsion into a three-necked flask, move it to an electric heating jacket with a mechanical stirrer, stir and react for 3.5h at 80℃ and 600rpm, and at the same time, add 12.9g of α-linolenic acid ethanol mixed solution at a rate of 3.5g / min, and the mass concentration of the α-linolenic acid ethanol mixed solution is 55%. The obtained solid-liquid mixture is filtered and rinsed with ethanol. The filtrate is placed in a blast drying oven at 65℃ for 30h to obtain a bioshell phase-change microcapsule.

[0049] Example 4

[0050] The same as Example 1, except that n-heptadecane is used instead of paraffin, and other reaction conditions and material composition remain unchanged to obtain biological shell material phase change microcapsules.

[0051] Example 5

[0052] The same as Example 1, except that vinyl stearate is used instead of paraffin, and other reaction conditions and material composition remain unchanged to obtain biological shell material phase change microcapsules.

[0053] Example 6

[0054] The same as Example 1, except that dextrorotatory menthol was used instead of levorotatory menthol, and other reaction conditions and material composition remained unchanged to obtain biological shell material phase change microcapsules.

[0055] Example 7

[0056] The same as Example 1, except that racemic menthol was used instead of L-menthol, and other reaction conditions and material composition remained unchanged to obtain biological shell material phase change microcapsules.

[0057] Example 8

[0058] The same as Example 1, except that polyethylene glycol 400 is used instead of polyethylene glycol 200, and other reaction conditions and material composition remain unchanged to obtain biological shell material phase change microcapsules.

[0059] Example 9

[0060] The same as Example 1, except that polysorbate-20 is used instead of polyethylene glycol 200, and other reaction conditions and material composition remain unchanged to obtain biological shell material phase change microcapsules.

[0061] Example 10

[0062] The same as Example 1, except that chloroform aqueous solution is used instead of ethanol aqueous solution, and other reaction conditions and material composition remain unchanged to obtain biological shell material phase change microcapsules.

[0063] Embodiment 11

[0064] The same as Example 1, except that acetone aqueous solution is used instead of ethanol aqueous solution, and other reaction conditions and material composition remain unchanged to obtain biological shell material phase change microcapsules.

[0065] Example 12

[0066] The same as Example 1, except that during the high-speed shear reaction, the reaction temperature was increased to 90° C., the reaction time was shortened to 3 min, the reaction speed was increased to 15000 rpm, and other reaction conditions and material composition remained unchanged, to obtain biological shell material phase change microcapsules.

[0067] Example 13

[0068] The same as Example 1, except that during the mechanical stirring reaction, the reaction temperature was lowered to 60° C., the reaction speed was increased to 700 rpm, the reaction time was extended to 5 h, and other reaction conditions and material composition remained unchanged, to obtain bioshell phase change microcapsules.

[0069] Embodiment 14

[0070] The same as Example 1, except that γ-linolenic acid is used instead of α-linolenic acid, and other reaction conditions and material composition remain unchanged, to obtain biological shell material phase change microcapsules.

[0071] Embodiment 15

[0072] The same as Example 1, except that linoleic acid is used instead of α-linolenic acid, and other reaction conditions and material composition remain unchanged, to obtain biological shell material phase change microcapsules.

[0073] Example 16

[0074] The same as Example 1, except that 9.5 g of α-linolenic acid ethanol mixed solution was added dropwise at a rate of 0.5 g / min, the mass concentration of the α-linolenic acid ethanol mixed solution was 70%, and other reaction conditions and material composition remained unchanged to obtain biological shell material phase change microcapsules. Example 17

[0075] The same as Example 1, except that the mass of the α-linolenic acid ethanol mixed solution is increased to 22.8 g, and other reaction conditions and material composition remain unchanged, to obtain biological shell material phase change microcapsules.

[0076] Embodiment 18

[0077] The method is the same as Example 1, except that acetone is used instead of ethanol in the filtration treatment stage of the obtained solid-liquid mixture, and other reaction conditions and material composition remain unchanged to obtain biological shell material phase change microcapsules.

[0078] Embodiment 19

[0079] The same as Example 1, except that during the forced air drying process, the drying temperature was increased to 100° C., the drying time was shortened to 12 h, and other reaction conditions and material composition remained unchanged, to obtain biological shell material phase change microcapsules.

[0080] Comparative Example 1

[0081] The same as Example 1, except that polyethylene glycol 200 was omitted during the preparation of the phase change microemulsion, and other reaction conditions and material composition remained unchanged to obtain the bioshell phase change microcapsules. The scanning electron microscope (SEM) photo of the bioshell phase change microcapsules prepared in Comparative Example 1 is shown in Figure 3 The differential scanning calorimetry (DSC) curve of the bioshell phase change microcapsules prepared in Comparative Example 1 is shown in Figure 5 .

[0082] Comparative Example 2

[0083] The same as Example 1, except that in the process of preparing the phase change microemulsion, an equal amount of deionized water was used instead of the ethanol aqueous solution, and other reaction conditions and material composition remained unchanged to obtain the bioshell phase change microcapsules. The scanning electron microscope (SEM) photo of the bioshell phase change microcapsules prepared in Comparative Example 2 is shown in Figure 4 .

[0084] Comparative Example 3

[0085] The same as Example 1, except that the α-linolenic acid ethanol mixed solution is not added dropwise, but directly poured into the phase change microemulsion for reaction, and other reaction conditions and material composition remain unchanged to obtain bioshell material phase change microcapsules.

[0086] Comparative Example 4

[0087] The same as Example 1, except that the α-linolenic acid ethanol mixed solution was omitted, and other reaction conditions and material composition remained unchanged, to obtain biological shell material phase change microcapsules.

[0088] Comparative Example 5

[0089] The same as Example 1, except that L-menthol was omitted, other reaction conditions and material composition remained unchanged, and biological shell material phase change microcapsules were obtained.

[0090] Comparative Example 6

[0091] According to the method described in CN111992153A, the aqueous phase octenyl succinate starch was dissolved in water, stirred in a constant temperature water bath at 90°C for 1 hour, and the starch was gelatinized into a transparent solution; the oil phase menthol was heated in a water bath at 80°C until it was completely melted. The oil phase was poured into the aqueous phase, homogenized and emulsified to obtain a pre-emulsion. The pre-emulsion was homogenized under high pressure, circulated for 5 rounds to obtain a hot nanoemulsion, and naturally cooled to room temperature. The cooled emulsion was fed into a peristaltic pump for spray drying, with a feed rate of 20 mL / min, to obtain a white microcapsule powder.

[0092] Comparative Example 7

[0093] According to the method described in CNCN105077249A, 26 kg of conjugated linoleic acid, 26 kg of modified corn starch and 78 kg of water were weighed and added to the emulsification kettle for emulsification for 30 minutes. The emulsion was then added to the high-speed homogenizer for shear homogenization. When the pressure reached 8 MPa to 10 MPa, the material was switched to the spray metering kettle. After homogenization, spraying was performed and the outlet temperature was controlled at 90°C to 120°C to obtain conjugated linoleic acid microcapsules.

[0094] Test Example 1

[0095] The physical and chemical properties of the bioshell material phase change microcapsules in Examples 1-19 and Comparative Examples 1-7 were measured, and the specific results are shown in Table 1.

[0096] Table 1 Properties of phase change microcapsules prepared in Examples and Comparative Examples

[0097] sample Average particle size / μm <![CDATA[Latent heat of fusion value / J·g -1 > <![CDATA[Latent heat of fusion value / J·g after 20 consecutive cycles -1 > Coverage rate / % <![CDATA[Thermal conductivity / W·m -1 ·K -1 > Compressive strength / MPa paraffin — 150.7 — — 0.12 — Example 1 10 120.0 117.5 79.6 0.45 2.0 Example 2 5 110.6 106.7 73.3 0.38 1.4 Example 3 20 115.2 111.0 76.4 0.42 1.6 Example 4 7 113.0 109.8 74.9 0.40 1.5 Example 5 10 108.6 104.5 72.0 0.34 1.2 Example 6 15 105.7 102.3 70.1 0.33 1.1 Example 7 20 104.6 100.8 69.4 0.33 1.0 Example 8 15 107.8 101.9 71.5 0.35 1.2 Example 9 18 105.0 100.8 69.6 0.34 1.0 Example 10 15 110.9 107.6 73.5 0.39 1.5 Embodiment 11 15 113.6 110.0 75.3 0.41 1.5 Example 12 7 103.6 100.0 68.7 0.34 1.1 Example 13 9 105.7 101.2 70.1 0.36 1.3 Embodiment 14 12 110.8 106.7 73.5 0.38 1.4 Embodiment 15 15 107.9 102.4 71.5 0.36 1.2 Example 16 20 103.9 100.1 68.9 0.33 1.0 Embodiment 17 15 105.8 101.6 70.2 0.35 1.1 Embodiment 18 12 115.5 112.3 76.6 0.42 1.7 Embodiment 19 12 112.8 108.6 74.8 0.39 1.5 Comparative Example 1 35 73.8 65.0 48.9 0.25 0.5 Comparative Example 2 40 65.7 58.2 43.5 0.23 0.3 Comparative Example 3 26 80.9 71.2 53.6 0.27 0.6 Comparative Example 4 1 75.6 67.3 50.1 0.26 0.4 Comparative Example 5 1.5 62.8 53.5 41.6 0.22 0.3 Comparative Example 6 22 — — — 0.25 0.5 Comparative Example 7 30 — — — 0.24 0.5

[0098] From Table 1, Figure 1-Figure 4It can be seen that the bioshell material phase-change microcapsules prepared by the present invention have good physical and chemical properties and regular microscopic morphology. In Example 1, the bioshell material is obtained by the esterification reaction of levomenthol and α-linolenic acid, and the encapsulation effect is firm, which is significantly better than the phase-change microcapsules prepared by using levomenthol (Comparative Example 4) or α-linolenic acid (Comparative Example 5) alone. At the same time, the bioshell material obtained by the esterification reaction of levomenthol and α-linolenic acid contains long-chain alkyl and cyclohexyl structural units, and has better mechanical strength than other types of bio-based phase-change microcapsules (such as Comparative Example 7). Figure 5 It can be seen that the latent heat of melting of the sample in Example 1 is 120 J / g. After 20 consecutive cycles of use, its latent heat of melting remains at 117.5 J / g, which is higher than the latent heat of melting of the comparative example sample. That is, the bioshell phase change microcapsules prepared by the present invention have better phase change heat storage and temperature control performance.

[0099] Test Example 2

[0100] The antibacterial properties, antioxidant properties and anti-ultraviolet radiation properties of the biological shell material phase change microcapsules in Example 1-2 and Comparative Example 1-2 were measured, and the specific results are shown in Table 2.

[0101] Table 2 Antibacterial and antioxidant properties of phase change microcapsules prepared in Examples and Comparative Examples

[0102] Anti-ultraviolet radiation performance

[0103] sample Staphylococcus aureus inhibition rate / % DPPH free radical scavenging rate / % Long wave UV absorbance Example 1 70 75 1.8 Example 2 65 70 1.5 Comparative Example 1 41 50 0.8 Comparative Example 2 37 46 0.6

[0104] It can be seen from Table 2 that the antibacterial, antioxidant and anti-ultraviolet radiation properties of the example samples are significantly higher than those of the comparative example samples, which indicates that the bioshell phase change microcapsules prepared by the method of the present invention have good functional service, which is consistent with the results in Table 1. The antibacterial rate of the example 1 sample against Staphylococcus aureus is 70%, the scavenging rate against DPPH free radicals reaches 75%, and its long-wave ultraviolet absorbance reaches 1.8.

Claims

1. A method for preparing a biological shell material phase change microcapsule, comprising the following steps: (1) uniformly mixing a molten phase change material, a shell material prepolymer A, a nonionic surfactant and a mixed solvent, and subjecting the mixture to a high-speed shear treatment to obtain a phase change microemulsion; (2) stirring the phase change microemulsion obtained in step (1) under heating and reacting, and simultaneously dropping a mixed solution containing the shell material prepolymer B to obtain a solid-liquid mixture; (3) filtering, washing, and drying the solid-liquid mixture obtained in step (2) to obtain bioshell phase change microcapsules; In step (1), the shell material prepolymer A is selected from one or more of levo-menthol, dextro-menthol, and racemic menthol; In step (2), the shell material prepolymer B is selected from one or more of α-linolenic acid, γ-linolenic acid, and linoleic acid.

2. The method according to claim 1, characterized in that: In step (1), the phase change material is selected from one or more of normal alkanes, paraffins, and stearates with a phase change temperature of 20°C to 30°C; the shell material prepolymer A is levomenthol; and the non-ionic surfactant is selected from one or more of polyethylene glycol 200, polyethylene glycol 400, and polysorbate 20.

3. The method according to claim 1, characterized in that In step (1), the phase change material is selected from paraffin with a phase change temperature of 20°C to 30°C; and the non-ionic surfactant is polyethylene glycol 200.

4. The method according to claim 1, characterized in that: In step (1), the mixed solvent is selected from one or more of ethanol aqueous solution, chloroform aqueous solution and acetone aqueous solution.

5. The method according to claim 1, characterized in that: In step (1), the mixed solvent is an ethanol-water solution, wherein the mass ratio of ethanol to water is 1:(5-15).

6. The method according to claim 4 or 5, characterized in that: In step (1), the mass ratio of ethanol to water in the ethanol aqueous solution is 1:(7-10).

7. The method according to claim 1, characterized in that In step (1), the mass ratio of the phase change material, the shell material prepolymer, the nonionic surfactant and the mixed solvent is 1: (0.1-0.8): (0.01-0.07): (15-35).

8. The method according to claim 1, characterized in that In step (1), the mass ratio of the phase change material, the shell material prepolymer, the nonionic surfactant and the mixed solvent is 1: (0.3-0.5): (0.03-0.05): (20-30).

9. The method according to claim 1, characterized in that: In step (1), the high-speed shearing treatment is carried out at a temperature of 50°C to 90°C for 3 minutes to 20 minutes, and a shearing speed of 7000rpm to 15000rpm.

10. The method according to claim 1, characterized in that In step (1), the high-speed shearing treatment has a shearing temperature of 65°C to 75°C, a shearing time of 7 min to 12 min, and a shearing speed of 9000 rpm to 13000 rpm.

11. The method according to claim 1, characterized in that: In step (2), the stirring reaction speed is 400 rpm to 700 rpm; the heating temperature is 60° C. to 90° C.; and the stirring reaction time is 1 h to 5 h.

12. The method according to claim 1, characterized in that In step (2), the stirring reaction speed is 500 rpm to 600 rpm; the heating temperature is 70° C. to 80° C.; and the stirring reaction time is 2.5 h to 3.5 h.

13. The method according to claim 1, characterized in that In step (2), the shell material prepolymer B is α-linolenic acid; the mixed solution containing the shell material prepolymer B is a mixed solution of the shell material prepolymer B and anhydrous ethanol, and the mass concentration of the shell material prepolymer B in the mixed solution is 35% to 70%; and the dripping rate is 2g / min to 20g / min per liter of phase change microemulsion.

14. The method according to claim 1, characterized in that In step (2), the mixed solution containing shell material prepolymer B is a mixed solution of shell material prepolymer B and anhydrous ethanol, and the mass concentration of shell material prepolymer B in the mixed solution is 45% to 55%; relative to each liter of phase change microemulsion, the dripping acceleration rate is 10g / min to 14g / min.

15. The method according to claim 1, characterized in that In step (2), the mass ratio of the shell material prepolymer B to the shell material prepolymer A in step (1) is 1:(0.35-0.95).

16. The method according to claim 1, characterized in that In step (2), the mass ratio of the shell material prepolymer B to the shell material prepolymer A in step (1) is 1:(0.5-0.7).

17. A biological shell material phase change microcapsule obtained by the preparation method according to any one of claims 1 to 16.

18. The biological shell material phase change microcapsule according to claim 17, characterized in that: The particle size of the biological shell material phase change microcapsule is 5μm-20μm, the melting latent heat value is 100J / g-120J / g, the coverage rate is 66.3%-79.6%, and the thermal conductivity is 0.33W·m -1 ·k -1 ~0.45W·m -1 ·K -1 , the compressive strength is 1MPa~2MPa.

19. The biological shell material phase change microcapsule according to claim 17 or 18, characterized in that: The antibacterial property of the biological shell material phase change microcapsule is that the antibacterial rate to Staphylococcus aureus is 60% to 70%, the scavenging ability of DPPH free radical is 65% to 75%, and the long-wave ultraviolet absorbance is 1.4 to 1.8.

Citation Information

Patent Citations

  • Conjugated linoleic acids capsule and preparation method thereof

    CN105077249A

  • Menthol microcapsule with high loading capacity and high thermal stability and preparation method thereof

    CN111992153A

  • Preparation method of menthol microcapsules

    CN101972619A

  • Linolenic acid microcapsules and preparation method thereof

    CN102429215A